Pengaruh Pengembangan Karir, Self-Efficacy Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Kantor Pusat PT Bank Sumut Medan - Parliando Saragih; Sarah Imelda (CV. Ulil Albab Corp, 2026)
This study aims to examine the influence of Career Development, Self-Efficacy, and Work Discipline on Employee Performance at the Head Office of PT Bank Sumut Medan. A quantitative approach was applied using a survey method. Data were collected through questionnaires distributed to permanent employees at the head office. Multiple linear regression analysis was used to determine the partial and simultaneous effects of the independent variables on employee performance. The results indicate that, partially, Career Development has a significant effect on Employee Performance, suggesting that well-managed career planning and development programs lead to higher employee performance. Self-Efficacy also shows a significant impact, indicating that employees' confidence in completing their tasks greatly contributes to their work effectiveness. Furthermore, Work Discipline significantly influences Employee Performance, revealing that adherence to rules, work schedules, and workplace ethics positively affects productivity. Simultaneously, the three variables have a very significant impact on Employee Performance, with an R Square value of 96%, meaning that the model explains almost all the variation in employee performance. These findings highlight the importance of an integrated human resource management approach to enhance overall employee productivity and performance.